2018
DOI: 10.1177/0143624418780633
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of photovoltaic arrays efficiency for reduction of building cooling load in hot climates

Abstract: This research work presents shading of building in hot and dry climate areas using rooftop photovoltaic arrays. Electrical power generation using photovoltaic arrays helps in reducing dependency on the utility grid. Areas with high intensities of solar radiation for a longer duration of time create high daily temperature. The Kingdom of Saudi Arabia (KSA) falls in high temperature and very low humidity climate zone. KSA has increased electricity tariff rates by 260% since 1 January 2018, has planned goals of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Zubair et al [38] examined the use and effectiveness of photovoltaic arrays in electrical power generation. This research showed that the most effective PV arrays are tilted PV arrays that provide electrical energy at a high-capacity factor while simultaneously saving building cooling energy by shading the rooftop.…”
Section: Renewable Energy In Saudi Arabiamentioning
confidence: 99%
“…Zubair et al [38] examined the use and effectiveness of photovoltaic arrays in electrical power generation. This research showed that the most effective PV arrays are tilted PV arrays that provide electrical energy at a high-capacity factor while simultaneously saving building cooling energy by shading the rooftop.…”
Section: Renewable Energy In Saudi Arabiamentioning
confidence: 99%
“…Photovoltaic is a very attractive option to generate onsite electricity in urban areas [11,12]. This solar energy technology produces electricity by direct conversion of sunlight to DC power [13].…”
Section: Introductionmentioning
confidence: 99%
“…The research study in [40] evaluated shading effect of rooftop PV on an office building in hot and dry climate. Another study [41] evaluated the performance of a rooftop PV system for a faculty building at Marmara University, Turkey. The proposed rooftop PV system had an average performance ratio of 72.9%.…”
Section: Introductionmentioning
confidence: 99%